Synthesis And Characterization Of Graphene Filled Epoxy And Pedot Pss Composites - Arshad, Norshamira (2018)
The discovery of graphene composites has driven changes among researchers because of their unique properties. The aim of the present study is to synthesize graphene and used as a filler in epoxy composites. The performance of synthesize graphene in epoxy was compared with commercialize graphene. Graphene was synthesized using modified Hummer’s method and spin coating was used to produce epoxy composites with varying amount of filler loading. Analysis from Raman spectrum of synthesize graphene showed an increase in intensity ratio (ID/IG) which indicates the decrease of average size of the sp2 domains upon reduction of the GO. This is due to the loss of carbon formation. Besides that, FTIR spectra showed that the graphite has been successfully oxidized due to the presence of peak which referring to oxygencontaining groups. The best graphene filler loading in epoxy composites was obtained at 0.4vol% based on thermal conductivity measurement which indicate 37.5% increment compared to unfilled epoxy. Additionally, graphene/epoxy composites shows that the addition of filler in epoxy generally increase the electrical conductivity value from 7.38 x 10-6 to 7.19 x 10-5 S/cm, which is two order of magnitude higher than unfilled epoxy. Graphene/PEDOT:PSS with 1.0vol% loading exhibits 90% and 81% improvement in electrical and thermal conductivities, respectively compared to graphene/epoxy composite.